Copper-doping effects in electronic structure and spectral properties of SmNi₅ - Knyazev, Yu.V.; Lukoyanov, A.V.; Kuz’min, Yu.I.; Kuchin, A.G. (Физика низких температур, 2015)
The electronic structure and optical properties of the SmNi₅₋Cux (x = 0, 1, 2) compounds are studied. The
band spectra of the studied intermetallics were calculated with LDA+U+SO method supplementing the local
density approximation with a correction for strong electron interaction on the shell of the rare-earth element. Optical
properties were studied by ellipsometry method in the wide wavelength range. It was found that the substitution
of copper for nickel leads to local changes in the optical conductivity spectra. Both the spectroscopic
measurements and theoretical calculations demonstrate the presence of a broad absorption band around 4 eV associated
with the Cu 3d → Ni 3d electron transitions and increasing with the grown of copper content. The experimental
dispersion curves of optical conductivity in the interband absorption region were interpreted using the
results of the calculations.